(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Participation in sports, particularly cricket and volleyball, offers numerous physical, mental, and social benefits for adolescents and young adults. However, the demands of competitive sports can also lead to stress and impact the overall wellbeing of young athletes. This paper presents a comprehensive review of the literature on the physical fitness levels, general wellbeing, and stress management strategies of under-nineteen cricket and volleyball players. It examines the unique challenges faced by young athletes and explores evidence-based interventions aimed at promoting their holistic development and performance. By synthesizing research findings and best practices, this review aims to provide insights and recommendations for supporting the physical and mental health of under-nineteen cricket and volleyball players.